2017
DOI: 10.1044/2017_jslhr-l-17-0121
|View full text |Cite
|
Sign up to set email alerts
|

False Belief Development in Children Who Are Hard of Hearing Compared With Peers With Normal Hearing

Abstract: Preschool-age CHH are at risk for delays in understanding others' beliefs, which has consequences for their social interactions and pragmatic communication. Research related to FB in children with hearing loss has the potential to inform our understanding of mechanisms that support social-cognitive development, including the roles of language and conversational access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 85 publications
(123 reference statements)
0
14
0
1
Order By: Relevance
“…Increased experience with linguistic input will result in more efficient language processing skills, whereas reduced auditory access will exacerbate risk for language delays. We have evidence to support this inconsistent access hypothesis in the areas of speech perception (McCreery, Walker, Spratford, Oleson, et al, 2015), global language development (Ambrose, Walker, Unflat-Berry, Oleson, & Moeller, 2015), morphosyntactic development (Koehlinger, Van Horne, & Moeller, 2013), and understanding of false belief (Walker, Ambrose, Oleson, & Moeller, 2017). This article was the first from the OCHL study to specifically examine whether auditory access impacts vocabulary knowledge.…”
Section: Factors Associated With Vocabulary Breadth and Depth In Chhmentioning
confidence: 91%
“…Increased experience with linguistic input will result in more efficient language processing skills, whereas reduced auditory access will exacerbate risk for language delays. We have evidence to support this inconsistent access hypothesis in the areas of speech perception (McCreery, Walker, Spratford, Oleson, et al, 2015), global language development (Ambrose, Walker, Unflat-Berry, Oleson, & Moeller, 2015), morphosyntactic development (Koehlinger, Van Horne, & Moeller, 2013), and understanding of false belief (Walker, Ambrose, Oleson, & Moeller, 2017). This article was the first from the OCHL study to specifically examine whether auditory access impacts vocabulary knowledge.…”
Section: Factors Associated With Vocabulary Breadth and Depth In Chhmentioning
confidence: 91%
“…Despite the improvements in early identification and intervention, some children with hearing loss (CHL) still lag behind children with normal hearing (CNH) in language ( McCreery et al, 2015 , Moeller et al, 2007 , Tomblin et al, 2015 , Tomblin et al, 2014 , Walker et al, 2020 ), cognitive ( Caudle et al, 2014 , Dye and Hauser, 2014 , Nittrouer et al, 2017 , Nittrouer et al, 2013 ), academic ( Khairi Md Daud et al, 2010 , Kouwenberg et al, 2012 , Theunissen et al, 2015 ), and psychosocial ( Dirks et al, 2017 , Netten et al, 2015a , Netten et al, 2015b , Theunissen et al, 2012 , Theunissen et al, 2014a , Theunissen et al, 2011 , Theunissen et al, 2015 , Walker et al, 2017 ) outcomes. It is important to note that these deficits are not universal; in fact, there is a considerable amount of variability in academic and language outcomes in CHL.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, ToM in DHH children has been studied since Peterson and Siegal’s (1995, 1999) research showed impaired false-belief understanding as a marker of mental-state understanding. The accumulating research, with few exceptions (e.g., Jones, Gutierrez, & Ludlow, 2015), shows ToM delays in DHH children with hearing parents (Peterson & Wellman, 2019; Walker, Ambrose, Oleson, & Moeller, 2017) and, as in language acquisition, not in those with deaf parents (i.e., native signers; Schick, De Villiers, De Villiers, & Hoffmeister, 2007). Some researchers have found that DHH children of hearing parents achieve an understanding of false belief between the ages of 7 and 8 years (e.g., Schick et al, 2007) of the sort that typically developing children develop at 4 and 5 years; others have found even larger delays (e.g., Marschark, Edwards, Peterson, Crowe, & Walton, 2018; Peterson, Wellman, & Liu, 2005).…”
mentioning
confidence: 99%